2016
DOI: 10.3111/13696998.2016.1141780
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic benefits of extended treatment with apixaban for the treatment and prevention of recurrent venous thromboembolism in Canada

Abstract: Background and objective Venous thromboembolism (VTE) is associated with long-term clinical and economic burden. Clinical guidelines generally recommend at least 3 months of anticoagulation, but, in clinical practice, concerns over bleeding risk often limit extended treatment. Apixaban was studied for extended VTE treatment in the AMPLIFY-EXT trial, demonstrating superiority to placebo in VTE reduction without increasing risk of major bleeding. This study assessed the long-term clinical and economic benefits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…From a cost perspective, the most important difference between the current study and the existing literature was the application of a pharmaceutical cost of $0.70 per day for VKA, rather than the $0.11 used in previous studies. 28,31 With respect to effectiveness, the current study found that DOACs (most notably apixaban) were more effective at generating QALY relative to LMWH + VKA than was the case in the previous literature. 28,31 This difference probably stems from the assumption in the current This single copy is for your personal, non-commercial use only.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…From a cost perspective, the most important difference between the current study and the existing literature was the application of a pharmaceutical cost of $0.70 per day for VKA, rather than the $0.11 used in previous studies. 28,31 With respect to effectiveness, the current study found that DOACs (most notably apixaban) were more effective at generating QALY relative to LMWH + VKA than was the case in the previous literature. 28,31 This difference probably stems from the assumption in the current This single copy is for your personal, non-commercial use only.…”
Section: Discussionmentioning
confidence: 49%
“…28,31 With respect to effectiveness, the current study found that DOACs (most notably apixaban) were more effective at generating QALY relative to LMWH + VKA than was the case in the previous literature. 28,31 This difference probably stems from the assumption in the current This single copy is for your personal, non-commercial use only. For permission to reprint multiple copies or to order presentation-ready copies for distribution, contact CJHP at cjhpedit@cshp.ca This single copy is for your personal, non-commercial use only.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…28,30,31 Two studies reported results in terms of a number of events among a cohort of 10 000 patients. 27,32 One study reported fatality rates and one study reported relative risk (RR) of recurrent VTE. 26,29 Most articles conducted univariate (1-way) sensitivity analysis to determine the impact of every single parameter used in the analysis model on the total medical cost estimated through the model.…”
Section: Resultsmentioning
confidence: 99%
“…29 Quon et al concluded that both major and CRNMB events were the main drivers for apixaban being the cost-effective choice among other DOACs. 27 Lanitis et al reported that apixaban…”
Section: Resultsmentioning
confidence: 99%